Exciton‐Induced Degradation of Hole Transport Layers and Its Effect on the Efficiency and Stability of Phosphorescent Organic Light‐Emitting Devices. Issue 5 (18th December 2018) - Yu, Hyeonghwa; Aziz, Hany
Abstract: The effect of exciton‐induced degradation of hole transport layers (HTLs) and its influence on efficiency and stability of phosphorescent organic light emitting devices (PhOLEDs) are investigated. In order to be able to isolate and study the effect of excitons on HTLs, UV illumination as a means to expose them to exciton stress is used. Results reveal that exciton stress of only the HTLs can lead to a significant deterioration in the electroluminescence external quantum efficiency and stability of PhOLEDs, revealing the detrimental role of exciton‐induced degradation of HTLs in limiting the device performance. The creation of quenchers in HTLs and the diffusion of excitons from the HTL to the EML appear to play roles in this degradation mechanism. Observations reveal that exciton‐induced degradation of HTLs more strongly impacts PhOLEDs than their fluorescent counterparts, revealing the more critical role that HTLs play in influencing their stability and pointing to the role of triplet excitons in this phenomenon. Observations also suggest that increasing the exciton stability of HTLs or reducing exciton lifetime in them can help increase device stability. The findings uncover a new degradation mode in PhOLEDs and provide key insights for device design for realizing better performance and stability. Abstract : The effect of exciton‐induced degradation of hole transport layers (HTLs) via UV radiation and its influence on the efficiency and stability of phosphorescent organic light‐emitting devices (PhOLEDs) are investigated. Results show that exciton stress of only the HTLs can lead to a significant deterioration in device performance.